SOCIAL PERCEPTIONS OF VOCAL AND FACIAL SEXUAL DIMORPHISM IN RELATION TO MATE CHOICE: ATTRACTIVENESS, FITNESS RISKS & INTRASEXUAL COMPETITION - O`Connor, JM Jillian (My University, 2013)
Previous research indicates that vocal and facial masculinity and femininity influence perceptions of attractiveness. Men generally perceive women with feminine traits as more attractive than less feminine women. This may be because women who possess more feminine traits are likely to be healthier and more fertile mates than are less feminine women. Masculine male traits also influence women’s perceptions of attractiveness. Although women do not always prefer masculine male traits, preferences for masculinity are observed under circumstances where women may gain the fitness benefits of heritable health and dominance. Masculine traits in men and feminine traits in women are further associated with the potential fitness risks of infidelity and reduced investment in mates. Here I address three previously unanswered questions concerning the influence of masculinity and femininity on social perceptions. First, how do male vocal and facial masculinity influence perceptions of attractiveness when these two traits are presented simultaneously? Second, does vocal masculinity influence perceptions of the potential fitness risks of infidelity and reduced relationship investment in mates? Third, do male masculinity and female femininity influence perceptions of potential same-sex rivals? In this dissertation I demonstrate that simultaneously presented male vocal and facial masculinity influence women’s perceptions of men’s attractiveness, that perceivers are somewhat aware of the potential fitness risks associated with preferring high quality mates, and that vocal and facial masculinity influence mate choice and intrasexual competition in similar ways. Overall, these studies demonstrate the pervasive influence of masculinity and femininity on mate-choice relevant social perceptions.
Keywords: voice; face; fundamental frequency; mate preferences; evolutionary psychology; Other Psychology; Other Psychology